First Experiences of Tapeba School Education: memories and stories (Research, Society and Development, 2021)
The article deals with the first experiences of tapebas schooling in the municipality of Caucaia, aiming to understand the aspects that led the tapeba indigenous people to start their schooling process. To support this study, we sought to base ourselves on theorists, laws and articles that address the indigenous theme. The choice of this topic was due to the master's belonging to the Tapeba ethnic group, who also had the guidance of Dr. Andrea Moura da Costa Souza and Dr. Anna Erika Ferreira Lima, professor of the Professional Master's Degree in Teaching and Teacher Training course UNILAB- IFCE. The methodology used in parts the bibliographical research, having as a qualitative approach in which it was used the application of a questionnaire (Google Forms) answered by three tapebas professors. During the readings for the writing of the work, we realized that the authors have an accurate look at the subject and that the teachers who participated in the questionnaire have a perception in line with the theoretical framework, leading us to understand in a comprehensive way the beginning of tapeba schooling, their struggles and demands.